High-Sustained Concentrations of Organisms at Very low Oxygen Concentration Indicated by Acoustic Profiles in the Oxygen Deficit Region Off Peru - Aurelien Paulmier; Gerard Eldin; José Ochoa; Boris Dewitte; Joël Sudre; Véronique Garçon; Jaques Grelet; Kobi Mosquera-Vásquez; Oscar Vergara; Helmut Maske (Frontiers in Marine Science, 2021)
The oxygen deficient mesopelagic layer (ODL) off Peru has concentrations below 5 μmol O 2 kg –1 and is delimited by a shallow upper oxycline with strong vertical gradient and a more gradual lower oxycline ( lOx ). Some regions show a narrow band of slightly increased oxygen concentrations within the ODL, an intermediate oxygen layer ( iO 2 ). CTD, oxygen and lowered Acoustic Doppler Current Profiler (LADCP, 300 kHz) profiles were taken on the shelf edge and outside down to mostly 2000 m. We evaluate here the acoustic volume backscatter strength of the LADCP signal representing organisms of about 5 mm size. Dominant features of the backscatter profiles were a minimum backscatter strength within the ODL, and just below the lOx a marked backscatter increase reaching a maximum at less than 3.0 μmol O 2 kg –1 . Below this maximum, the acoustic backscatter strength gradually decreased down to 1000 m below the lOx . The backscatter strength also increased at the iO 2 in parallel to the oxygen concentration perturbations marking the iO 2 . These stable backscatter features were independent of the time of day and the organisms represented by the backscatter had to be adapted to live in this microaerobic environment. During daylight, these stable structures were overlapped by migrating backscatter peaks. Outstanding features of the stable backscatter were that at very low oxygen concentrations, the volume backscatter was linearly related to the oxygen concentration, reaching half peak maximum at less than 2.0 μmol O 2 kg –1 below the lOx , and the depth-integrated backscatter of the peak below the lOx was higher than the integral above the Ox. Both features suggest that sufficient organic material produced at the surface reaches to below the ODL to sustain the major fraction of the volume backscatter-producing organisms in the water column. These organisms are adapted to the microaerobic environment so they can position themselves close to the lower oxycline to take advantage of the organic particles sinking out of the ODL.